2020
DOI: 10.3390/metabo11010005
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Glucose and Heart Rate Monitoring in Young People with Type 1 Diabetes: An Exploratory Study about Perspectives in Nocturnal Hypoglycemia Detection

Abstract: A combination of information from blood glucose (BG) and heart rate (HR) measurements has been proposed to investigate the HR changes related to nocturnal hypoglycemia (NH) episodes in pediatric subjects with type 1 diabetes (T1D), examining whether they could improve hypoglycemia prediction. We enrolled seventeen children and adolescents with T1D, monitored on average for 194 days. BG was detected by flash glucose monitoring devices, and HR was measured by wrist-worn fitness trackers. For each subject, we com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…So far, HRV during nocturnal hypoglycemia has not been studied in children. However, one recent study reported a change in heart rate before nocturnal hypoglycemia compared to euglycemia 25 …”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…So far, HRV during nocturnal hypoglycemia has not been studied in children. However, one recent study reported a change in heart rate before nocturnal hypoglycemia compared to euglycemia 25 …”
Section: Discussionmentioning
confidence: 97%
“…This is particularly important, as there is evidence, that children with T1D have longer QTc intervals than healthy controls 28–30 . A recent study even found prolonged QTc intervals (>450 ms) in one‐third of children with T1D 25 . A superimposed additional QTc prolonging effect of hypoglycemia could be critical in those children.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations